Biopsychosocial determinants of depression among the male inmates in Malaysia - Minhat, Halimatus Sakdiah; Subbarao, Gunenthira Rao (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: The increasing prevalence of depression has been a major public health concern. Being a marginalized population put the inmates at risk of depression. The main objective of this study was to identify the determinants of depression among the inmates according to the biopsychosocial model. Methods: A cross sectional study involving 460 male inmates was conducted at a medium security prison in Seremban. Only Malaysian adult prisoners who have been convicted and had spent a minimum of three months in the prison were eligible for the study. They were selected using the probability proportional to size using stratified random sampling. Data was collected using validated and pre-tested questionnaire by face-to-face interviews, with depression was measured using the Center for Epidemiologic Studies Depression (CES-D) Scale. The data were analyzed using IBM SPSS version 22 with a p-value less than 0.05 was considered statistically significant. Results: The results showed prevalence of depression were 40.70% (95% CI: 36.21-45.19) with its development being predicted by presence of communicable disease (AOR=2.145, 95% CI: 1.123-4.095), history of childhood abuse (AOR=1.762, 95% CI: 1.045-2.972), sentences of more than 5 years (AOR=3.801, 95% CI: 1.529-9.450), being non-Muslims (AOR=2.261, 95% CI: 1.461-3.497) and perceived stress (AOR=4.007, 95% CI= 2.610-6.151). Conclusions: This study revealed an alarmingly high prevalence of depression among the male inmates, with stress being the strongest risk factor. Reintegration of the prisoners into the community should be considered as part of the rehabilitation program to ensure continuation of psychiatric care and reduce relapsing.